Can edaphic variables improve DTPA-Based zinc diagnosis in corn? - Barbieri, Pablo; Sainz Rozas, Hernan Rene; Wingaard, Nicolás; Eyherabide, Mercedes; Reussi Calvo, Nahuel Ignacio; Salvagiotti, Fernando; Correndo, Adrián A.; Barbagelata, Pedro Anibal; Espósito Goya, Gabriel Pablo; Colazo, Juan Cruz; Echeverria, Hernan Eduardo (2017)
Current zinc (Zn) diagnostic methods for corn (Zea mays L.) are often based on soil DTPA (diethylenetriamine-pentaacetic acid) extractable Zn (DTPA-Zn). However, calibration of the DTPA-Zn test may be influenced by other soil properties such as pH, organic matter (SOM) and available Bray-P (PBray-1). Our objective was to assess the contribution of soil properties to a DTPA-Zn model used to predict corn response to Zn fertilization. We conducted 64 field trials with two Zn-fertilization treatments: with and without Zn fertilization. In all sites, we measured SOM, PBray-1, pH, and DTPA-Zn at 0- to 20-cm depth before sowing. Yield difference between Zn-fertilized and unfertilized treatments (Ydifference) was significant in 33% of the experimental site-years. In responsive site-years, the average Ydifference was 0.98 Mg ha-1 (11.4%). Soil organic matter was the only property that was a significant addition to the DTPA-Zn model for predicting the corn relative yield (Model R2 including SOM = 0.27). However, the improvement was nominal (Partial R2 of SOM = 0.06). Use of DTPA-Zn alone was suitable to discriminate Zn responsiveness among site-years based on the Ydifference by correctly diagnosing 81% of the outcomes. We determined three soil DPTA-Zn ranges with different probability of resulting in a Ydifference greater than zero when fertilized with Zn: high (<0.9 mg kg-1), medium (0.9–1.3 mg kg-1), and low (>1.3 mg kg-1). These soil-test-based Zn recommendations improve the identification of Zn-deficient soils allowing prevention of yield loss from Zn deficiency and more rational use of Zn fertilizers.